2014
DOI: 10.2478/pjvs-2014-0028
|View full text |Cite
|
Sign up to set email alerts
|

Is adenomyosis a problem in reproduction and fertility?

Abstract: Adenomyosis is defined as the presence of glandular foci beside the endometrium of uterus: in the myometrium and/or perimetrium depending on the progress of the disorder. So far, adenomyosis has been diagnosed in women and rodents, and studies conducted on cows have been rare. In this review we: (1) summarize the knowledge regarding adenomyosis, (2) compare the symptoms and aetiopathology between women and cows, (3) describe angiogenic uterine processes related to adenomyosis development and (4) outline the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…According to this hypothesis, glandular nests may arise de novo within the myometrial layer from undifferentiated stem cells under specific conditions, in particular under the influence of oestradiol (E 2 ) [ 7 , 8 ]. Whatever the mechanism underlying formation of glandular foci in the myometrium, hormonal and immunological abnormalities certainly play a role during adenomyosis development [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to this hypothesis, glandular nests may arise de novo within the myometrial layer from undifferentiated stem cells under specific conditions, in particular under the influence of oestradiol (E 2 ) [ 7 , 8 ]. Whatever the mechanism underlying formation of glandular foci in the myometrium, hormonal and immunological abnormalities certainly play a role during adenomyosis development [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a special form of endometriosis, the typical clinical features of adenomyosis include menorrhagia, dysmenorrhea, metrorrhagia and infertility (1)(2)(3). The medications most commonly used to treatments for adenomyosis are hormonal, including the levonorgestrel intrauterine system and gonatropin-releasing hormone agonists.…”
Section: Introductionmentioning
confidence: 99%
“…These days of the estrous cycle were selected for experiments because this study is continuation of our concerning adenomyosis (Korzekwa et al 2013(Korzekwa et al , 2014(Korzekwa et al , Łupicka et al 2015 and adenomyosis has been observed during the luteal stage of the estrous cycle in cattle (Moreira et al 2007). Uterine tissues were obtained at the Meat Processing Plant "Warmia" (Biskupiec, Poland) and transported on ice to the laboratory within 40 min.…”
Section: Materials Collectionmentioning
confidence: 99%
“…Adenomyosis is a uterine dysfunction characterized by the presence of endometrial glands with stromal elements in the myometrium (Azziz 1989, Campo et al 2012) but the etiology of this disorder is still unclear (Ferenczy 1998, Korzekwa et al 2014. Our previous studies showed that in cows the freCorrespondence to: A. Korzekwa, e-mail: a.korzekwa@pan.olsztyn.pl, tel.…”
Section: Introductionmentioning
confidence: 99%